2018
DOI: 10.1021/acs.inorgchem.8b00061
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pressure on the Microstructure and Simultaneous Optimization of the Electrical and Thermal Transport Properties of Yb0.5Ba7.5Ga16Ge30

Abstract: The thermoelectric (TE) properties of n-type polycrystalline YbBaGaGe bulks can be optimized by high-pressure and high-temperature (HPHT) sintering. After HPHT sintering, abundant nanograins are randomly distributed in the sample. Grains are refined by HPHT, with the grains being smaller with higher pressure. In comparison with the arc-melted sample, the samples obtained by quenching under high pressure possess a great number of nanograins and lattice structural disorders. Lower thermal conductivity is benefit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 31 publications
(36 reference statements)
0
17
0
Order By: Relevance
“…59 These led to significant improvements in its power factor to ∼3.4 mW K −2 m −1 and its figure of merit to ZT ∼ 0.75 at 7 GPa. 59 A study of Yb 0.5 Ba 7.5 Ga 16 Ge 30 synthesized under HP-HT conditions showed that at a synthesis pressure of 5 GPa, this thermoelectric material possessed a maximum value of ZT ∼ 1.13 at 773 K. 161 Little attention has been paid to the high-pressure thermoelectric properties of other thermoelectric materials incorporating Group IV elements, for example, Si 1−x Ge x alloys. 162,163 However, experimental studies on high-quality single crystals of Ge-and Ge-doped Si showed that the pressure dependence of their Seebeck coefficients may be quite spectacular.…”
Section: Non-chalcogenide Thermoelectric Materialsmentioning
confidence: 99%
“…59 These led to significant improvements in its power factor to ∼3.4 mW K −2 m −1 and its figure of merit to ZT ∼ 0.75 at 7 GPa. 59 A study of Yb 0.5 Ba 7.5 Ga 16 Ge 30 synthesized under HP-HT conditions showed that at a synthesis pressure of 5 GPa, this thermoelectric material possessed a maximum value of ZT ∼ 1.13 at 773 K. 161 Little attention has been paid to the high-pressure thermoelectric properties of other thermoelectric materials incorporating Group IV elements, for example, Si 1−x Ge x alloys. 162,163 However, experimental studies on high-quality single crystals of Ge-and Ge-doped Si showed that the pressure dependence of their Seebeck coefficients may be quite spectacular.…”
Section: Non-chalcogenide Thermoelectric Materialsmentioning
confidence: 99%
“…78 Recently, it has been successfully demonstrated that the Ge-based clathrate compound Yb 0.5 Ba 7.5 Ga 16 Ge 30 synthesized under a pressure of 5 GPa and a temperature of 773 K has a higher ZT value of 1.13. 79 These results show that, compared with other materials, type I clathrates still have complex and diverse situations in terms of improving the thermoelectric performance.…”
Section: Sintering Temperature (K)mentioning
confidence: 87%
“…8a) or arc-melting chamber. 47 ture of 1600-1800°C. 48 Some borides, including WB 3 , 49 MnB, 50 Mn 3 B 4 , 51 and MoB 4 , 52 were also synthesized successively with a high pressure and high temperature method.…”
Section: Element Reaction Routementioning
confidence: 99%